Broadband applications and the digital home - Turnbull, John (John G.).; Garrett, Simon (Simon G. E.). (London, United Kingdom Institution of Engineering and Technology, 2003)
This book has 17 chapters and divided into 5 parts. The first part covers topics on delivery to the home, the second part covers topics on networking the home, the third part covers topics on living in the home, the fourth part covers the applications of the broadband networks and the fifth part covers topics on future digital home.
Electronic reproduction.
Keywords: Broadband communication systems; Electronic books